Análisis comparativo de la velocidad de corrosión de un inhibidor verde en un acero API 5LX65 (2024)
Corrosion, a natural process that deteriorates metals by electrochemical reactions in the presence of moisture and corrosive agents, can be combated with inhibitors. These act as modifiers of electrochemical reactions, significantly reducing the corrosion rate and protecting metals from deterioration. In the following project, various topics will be presented about corrosion and its consequences, corrosion inhibitors along with types, categories, and industrial uses. Simultaneously, the exposure to studies that are carried out to evaluate corrosion using different electrochemical techniques and the selection of the green inhibitor based on a guava leaf extract, deepening about potentiodynamic polarization and its application for the specific type of steel to work on which is the API 5L X65, this steel was metallographically characterized for its microstructure with and without the inhibitor, evidencing that there was a decrease in general and pitting corrosion. Finally, after carrying out the electrochemical tests, it was determined that the selected green inhibitor reduces the corrosion rate in API 5L X65 steel in a 3.56% NaCl saline aqueous medium.